272Transdiagnostic Risk and Protective Factors for Psychopathology in Young People: A systematic review. (2nd September 2021) - Lynch, Miss Samantha; Sunderland, Matthew; Newton, Nicola C; Chapman, Cath
Abstract: Focus of Presentation: Mental health and substance use disorders are among the leading causes of burden of disease worldwide. These disorders often emerge during adolescence, with risk of onset peaking between the ages 13 and 24. Despite decades of research, the underlying causes of mental health disorders remain unclear. This in part may be due to limitations of existing, categorical diagnostic systems, such as low specificity demonstrated by the high rates of co-occurring mental health disorders. A growing body of research supports a move towards dimensional, empirically derived models of psychopathology, such as the Hierarchical Taxonomy of Psychopathology (Hi-TOP) model. The present systematic review seeks to identify risk and protective factors for psychopathology in young people that occur across traditional diagnostic categories by synthesising and evaluating findings from research investigating empirically based models of psychopathology. Findings: Findings will be summarised in a narrative synthesis and grouped by broad research domain, such as genetic, neurobiological, cognitive social and environmental. Conclusions/Implications: The implications of these findings for the development of prevention and early intervention programs will be discussed. Key messages: Empirically based models of psychopathology provide a vital opportunity to advance our knowledge of the risk and protective factors for mental health and substance use disorders, and in turn lead to the development or enhancement of prevention programs.